Metaverse Economy: Redefining Consumer Experience and Business Models - Nova Yuningrat (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
The development of immersive technologies such as virtual reality (VR) and augmented reality (AR) has given birth to the metaverse phenomenon that redefines consumer interaction with brands and companies. The metaverse not only offers new experiences based on presence, avatars, and co-creation, but also drives the transformation of digital business models. However, empirical evidence on how consumer experience affects loyalty and monetization mechanisms in the context of the metaverse is still limited. This research aims to identify the factors that shape the consumer experience in the metaverse, analyze the relationship between technology adoption, immersive experience, and business model performance, and formulate strategic design guidelines for companies. The research method uses a quantitative approach with a survey of 200 metaverse users in Indonesia. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the support of qualitative interview data to strengthen interpretation. The results showed that presence, embodiment, and co-creation had a significant effect on engagement with a contribution of 64%. Technology acceptance factors (performance expectancy, social influence, and facilitating conditions) explain 58% of loyalty variance. In addition, the configuration of business models based on experience-as-a-service, community subscriptions, and tokenization was able to explain the 61% variance of willingness to pay. The implications of this study confirm that the metaverse economy is not just a technological phenomenon, but a new economic system that requires companies to design consumer experience strategies, technology acceptance, and business models in an integrated manner